Real face of Hinduism Book states the cardinal tenets of pristine Hinduism in a nutshell, in an attempt to set aside the widespread misunderstanding about this religion - Katti, Raghavendra (Pune Dr. Raghavendra Katti, 2018)
Problems with vedic literature